Normal and histopathological organization of the opercular bone and vertebrae in gilthead sea bream Sparus aurata - Ortiz-Delgado, Juan B. (2018)
This study provides a comprehensive description of the tissue organization of non-deformed and deformed opercula and vertebrae from gilthead sea bream Sparus aurata juveniles by means of histological, histochemical and immunohistochemical approaches. Two types of opercular anomalies are described: the folding of the opercle and subopercle into the gill chamber, starting at the upper corner of the branchial cleft and extending down to its lower third; and the partial lack of the operculum (opercle, subopercle, interopercle and preopercle underdeveloped) with a regression of the loose edge extending down to its lower third. Histological observations revealed a rare type of bone remodelling process in the opercular structure, which consisted of the coalescence of contacting bone tissues (presumably from the preopercle and opercle), resulting in skeletal tissue with a trabecular aspect filled by a single-cell epithelium of cubic osteoblastic-like cells. Differences in collagen fiber thickness and its 3-dimensional arrangement between normal and deformed opercula were also found. Lordotic vertebrae were characterized by the formation of fibrous cartilage in the haemal and/or neural sides, indicating that a metaplastic shift occurred during the process of lordosis. Another major histomorphological change found in lordotic vertebrae was the complete loss of notochordal sheath integrity. Histological alterations were coupled with an imbalance of cell death and cell proliferation processes in lordotic vertebrae as well as that of bone formation/resorption, and extracellular matrix deposition activity differences which might have resulted from the remodelling process occurring in lordotic vertebrae. Altogether, these results provide an increase in our basic knowledge of bone disorders that contribute to our understanding of the mechanisms by which these skeletal anomalies appear in this fish species and which hamper its production efficiency.